The Contagion of the Subprime Crisis in the Sector Indices of the Brazilian Stock Market: An Approach to Multivariate Conditional Volatility Models - Ferreira, Douglas Marcos (2023)
Oscillations within the financial market during the subprime crisis caused an increase in volatility and a fall in asset prices, in addition to increasing the degree of normal market movements. This study analyzed the contagion effect of the international financial crisis on the Brazilian stock market indices upon studying the estimated covariance patterns between the Brazilian and American stock market indices. The empirical analysis was based on the multivariate BEKK-GARCH models. The results showed that the estimation of the covariance structure between 2007 and 2010 had clear evidence of contagion in the indices investigated: Electricity (IEE), Telecommunications (ITEL), Consumption (ICON), Industrial Sector (INDX), Real Estate (IMOB), and Financial (IFNC). During the period of the international financial crisis, there was an increase in the covariance between the American and Brazilian market indices. The IMOB and IFNC indices showed the highest contagions among all the ones analyzed, reflecting the losses of the civil construction industry along with internal and external credit scarcity.